People and spaces in Roman military bases - Allison, Penelope M. 1954- (Cambridge University Press, 2013)
This study uses artefact distribution analyses to investigate the activities that took place inside early Roman imperial military bases. Focusing especially on non-combat activities, it explores the lives of families and other support personnel who are widely assumed to have inhabited civilian settlements outside the fortification walls. Spatial analyses, in GIS-type environments, are used to develop fresh perspectives on the range of people who lived within the walls of these military establishments, the various industrial, commercial, domestic and leisure activities in which they and combat personnel were involved, and the socio-spatial organisation of these activities and these establishments. The book includes examples of both legionary fortresses and auxiliary forts from the German provinces to demonstrate that more material-cultural approaches to the artefact assemblages from these sites give greater insights into how these military communities operated and demonstrate the problems of ascribing functions to buildings without investigating the full material record